Athar Istīʿāb al-Mufradāt wa-al-Qawāʿid ʿalá Kafā’at al-Kitābah al-Imlā’īyah li-al-Talāmīdh fī al-Faṣl al-Thāmin bi-Madrasat Al-Waṭanīyah al-Thānawīyah al-Islāmīyah Kebumen - Fiki Khoerun Niswah; Ibnu Hadjar; Mahfudz Shiddiq (Alsina : Journal of Arabic Studies, 2021)
Many students at Wathoniyah Islamiyah Junior High School (Madrasah Tsanawiyah) Kebumen graduated from public elementary schools, so many had not have adequate knowledge of the Arabic language. This study is essential because students' diverse vocabulary and grammatical comprehension influenced their writing and spelling ability. The current study investigates the influence of vocabulary and grammatical comprehension on eighth grade students' spelling writing abilities at Wathoniyah Islamiyah Kebumen. All eighth-grade students at Wathoniyah Islamiyah Junior High School were recruited in this research. The study employed a quantitative design and purposive sampling technique to test the sample. The researchers obtained the data using documentation and analyzed the data using multiple regression tests. The results indicated that the F value is 11.250, and the F table with the value from the table at a 5% significance level = 3.385. Therefore, the F count exceeds the F table. The findings also indicated that the students' vocabulary and grammatical knowledge and comprehension have a substantial influence on their spelling and writing skill. Therefore, the research hypothesis is acceptable.